Using strengths to attack weaknesses – The effect of comparative advertising on purchasing intention of green products - Ni, Kuocheng; Lin, Yanfeng; Ye, Shenghong; Lin, Zhiheng; Liu, Yunxiao (Frontiers in Psychology, 2022)
Firms increasingly use comparative advertising in green marketing to convey information of green products to consumers, but there is still a lack of research on the effect and mechanism of comparative advertising in the green products field. Across four experimental studies, we show that comparative advertising facilitates consumers’ purchase intention of green products, because comparative advertising lead to higher perceived diagnosticity of Information. Yet, comparative advertising does not always bring high intention to buy green products. When using egoistic appeals, the perceived diagnosticity of information and purchase intention of green products were higher in comparative advertising than in non-comparative advertising. When utilizing altruistic appeals, there was no significant difference between the two kinds of advertising. In addition, individual differences of consumers also affect the effect of comparative advertising. The positive effect of comparative advertising on the purchase intention of green products is weakened for consumers with high green involvement. Our findings advance existing knowledge about the use of comparative advertising in green marketing and provide enlightening suggestions for how firms can promote consumers to buy green products.